Effect of Temperature on Production of Ochratoxin A by Aspergillus niger in Orange Juice. (28th January 2014) - Marino, Andreana; Fiorentino, Caterina; Spataro, Francesca; Nostro, Antonia
Abstract : This challenging study was carried out to evaluate the temporal production of ochratoxin A (OTA) by Aspergillus niger ATCC 16404 and wild type A. niger AM at different temperatures in fresh squeezed orange juice ( Citrus sinensis [L.] Osbeck cv Tarocco). Each strain, inoculated into the filtered orange juice, was incubated at 4°C, 20°C, and 26°C for 28 days. In the juice, at 26°C and 20°C, the concentration of A. niger ATCC 16404 increased by more than 2 log10 up to the 21st day. At 4°C it remained constant. The microbial load of A. niger AM decreased at all temperatures. At 26°C, the maximum OTA accumulation found was 3.44 ng/mL on the 21st day for A. niger ATCC 16404 and 8. 44 ng/mL on the 7th day for A. niger AM. The OTA synthesis seemed to be an intrinsic strain-dependent mechanism. A. niger ATCC 16404 produced OTA in accordance with the higher temperatures and the biomass concentrations, whereas A. niger AM produced the toxin at all temperatures regardless of its biomass. These results showed that fresh orange juice contaminated with Aspergillus niger aggregate strains may contain OTA levels.